ANALISIS PENDAPATAN USAHATANI KAKAO DI DESA TARIPA KECAMATAN SINDUE KABUPATEN DONGGALA - Amalia, Amalia; Sulaeman, Sulaeman; Muhsin, Karlina (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
This study aimed to analyze the income derived from cocoa farming by farmers in Taripa Village, Sindue Subdistrict, Donggala Regency. A simple random sampling method was employed to select respondents, resulting in a sample size of 33 farmers out of a total population of 128 cocoa farmers. The primary analytical tool used in this study was the farming income analysis method. The findings indicated that the average income of farmers in Taripa Village is IDR 17,352,045.55/0.74 ha, or IDR 23,448,710.20/ha. The average revenue received was IDR 18,754,545.45/0.74 ha, or IDR 25,261,224.49/ha, with the average total cost amounting to IDR 1,402,499.91/0.74 ha, or IDR 1,895,270.15/ha at the average price of cocoa was IDR 30,000 per kg